2020
DOI: 10.1093/eurpub/ckaa165.1132
|View full text |Cite
|
Sign up to set email alerts
|

Are contextual socioeconomic factors associated with diarrhea in Mozambique children under age 5?

Abstract: Background Diarrhea is still highly prevalent in Mozambique children under age 5, which leads to avoidable morbidity and mortality. Specific socio-economic variables may influence diarrhea prevalence. Methods Secondary data analysis with the application of multiple logistic regression models on the data of 10026 living children under age 5 from Mozambique's Demographic Health Survey (DHS) report from 2011. Data were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…In this study, the prevalence of childhood diarrheal diseases was 22.5% over two weeks. This finding is higher than studies conducted elsewhere in the SADC region (6,16). A study conducted in a South African low-and middle-income township (Soweto) found a diarrheal disease prevalence of 20.9% among children under-5 years old (16).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In this study, the prevalence of childhood diarrheal diseases was 22.5% over two weeks. This finding is higher than studies conducted elsewhere in the SADC region (6,16). A study conducted in a South African low-and middle-income township (Soweto) found a diarrheal disease prevalence of 20.9% among children under-5 years old (16).…”
Section: Discussionmentioning
confidence: 61%
“…This study's prevalence was higher when compared to a study in Mozambique with a similar population that find a prevalence of 10.6%. of the 10026 children under the age of five had diarrhea (6). However, it was lower when compared to a conducted in Zambia, with a prevalence of 29 .1% (17).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In this study, the prevalence of childhood diarrheal diseases was 25.1% over two weeks. This finding was higher than studies conducted elsewhere in the Southern African Development Community (SADC) region [6,18]. A study conducted in a South African low-and middle-income township (Soweto) found a diarrheal disease prevalence of 20.9% among children under 5 years old [18].…”
Section: Discussionmentioning
confidence: 68%
“…Scientific evidence shows that a lack of sanitation facilities, urbanization, clean drinking water, proper waste disposal (including sewage), and living conditions contribute to the occurrence of diarrheal diseases. Furthermore, social determinants such as household economic status, parents' characteristics, and behaviour have been linked to diarrheal disease [5,6].…”
Section: Introductionmentioning
confidence: 99%